Analisis Yuridis Pelaksanaan Sanksi Denda Tilang pada Electronic Traffic Law Enforcement (E-TLE) terhadap Pelaku Pelanggar Lalu Lintas menurut Undang-Undang Nomor 22 Tahun 2009 tentang Lalu Lintas dan Angkutan Jalan (Studi Kasus di Wilayah Hukum DITLANTAS - Rosy, Deuis Rina; Yunara, Edy; Mulyadi, Mahmud; Sihombing, Eka Nam (Gorontalo Law Review, 2025)
Electronic Traffic Law Enforcement (E-TLE) is an electronic-based traffic law enforcement system that aims to increase the effectiveness of monitoring traffic violations. Although the implementation of E-TLE in Indonesia is based on Law Number 22 of 2009 concerning Road Traffic and Transportation, its implementation in several regions, including Medan City, has not run optimally. This study aims to analyze the legal basis of E-TLE, the application of ticket fines to traffic violators, and identify obstacles and resolution efforts so that the implementation of E-TLE runs effectively in Medan City. The research method used is empirical juridical method with a qualitative approach. The research data were obtained through interview studies and online questionnaires involving the community and the North Sumatra Police Traffic Directorate, and supported by a review of related regulations and literature. The results showed that the implementation of E-TLE has not been effective due to various obstacles, such as limited facilities and infrastructure, underutilization of human resources, the influence of weather, and the lack of synergy between local governments, police, and the community. These obstacles indicate the need for improvement in terms of technical and policy to support the optimal success of E-TLE implementation.